Latin America as a White Settler Society. - GOTT, RICHARD (Bulletin of Latin American Research, 2007)
Latin America’s nineteenth century history of Europeanisation, immigration and extermination suggests that the continent should fit neatly into the category of ‘settler colonialism’, a notion usually employed to describe the white settler colonies of European empires other than those of Spain and Portugal. While the last years of empire and the early days of the republics saw efforts to include the indigenous population as citizens, the racist white elites in the century after independence sought to import European migrants to prevent the non-white population from participating in power. The desired ‘whitening’ of the population was rarely successful, but the weight of white immigration helped create a twentieth century society that ignored the indigenous peoples – until the popular explosions of recent years.